Writing an invited review - Peh, W.C.G.; Ng, K.H. (2010)
An invited review provides a detailed and comprehensive narrative analysis of recent developments in a specific topic, and highlights important points that have been previously published. It usually consists of a short unstructured abstract, introduction, subheadings to organise the topic, and a summary. The text is usually relatively long compared to other paper categories, typically up to 15 manuscript pages or 4,000 words. The reference list is expected to comprehensively cover all the major published work, with up to 50-75 references being typical. The ideal invited review should be topical, current, balanced, accurate, quotable and easily understood, with clear take-home messages.